Agricultural use of phonolite and verdete rocks as a source of k for corn crop - Souza Pessoa, Rodrigo; Zonta, Everaldo; Aziz Alexandre Pozza, Adélia; da Silva Moretti, Bruno; de Fátima Silva Pessoa, Viviane; Vasconcellos Inda, Alberto (Revista Ceres, 2023)
This study aimed to evaluate the effect of the application of Siliceous Rocks Powder as a source of K (phonolite and verdete) in natura and calcined at temperatures of 300, 600, 800 and 1000° C, pure and in consortium with dolomitic limestone and coffee husk to corn crop (Zea mays L.). The analyses of the phenological variables, stem diameter, number of shoots, leaves, plants height, weight of dry biomass of the aerial part and the contents of N, P and K, accumulated in the aerial part of the plants were performed. The range of calcination temperature between 300 °C and 600 °C, being the treatments that become K more available to the plants. The treatment that produced the highest biomass was the rocks in mixture (m/m) with coffee husk. The calcination temperatures influenced the biomass production and the content of macronutrients accumulated in the dry biomass of the aerial part. The least efficient treatment in the production of biomass was associated with the rocks in mixture with dolomitic limestone.